1994
DOI: 10.1128/jvi.68.4.2051-2058.1994
|View full text |Cite
|
Sign up to set email alerts
|

An influenza A (H1N1) virus, closely related to swine influenza virus, responsible for a fatal case of human influenza

Abstract: , an influenza A virus, designated A/Maryland/12/91 (A/MD), was isolated from the bronchial secretions of a 27-year-old animal caretaker. He had been admitted to the hospital with bilateral pneumonia and died of acute respiratory distress syndrome 13 days later. Antigenic analyses with postinfection ferret antisera and monoclonal antibodies to recent Hi swine hemagglutinins indicated that the hemagglutinin of this virus was antigenically related to, but distinguishable from, those of other influenza A (HlNl) v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(32 citation statements)
references
References 46 publications
0
32
0
Order By: Relevance
“…Human-swine reassortant viruses have been detected in pigs in Japan, Europe, and the United States, demonstrating that genetic reassortment can occur in nature between influenza A viruses in pigs, but these resulting reassortants have not yet resulted in an epidemic virus strain in humans (162). While swine influenza viruses have been sporadically transmitted to humans, none of these incidents has resulted in an epidemic disease in humans (35,39,54,55,60,78,81,98,155,193,201,225).…”
Section: History Of Influenza Pandemicsmentioning
confidence: 99%
“…Human-swine reassortant viruses have been detected in pigs in Japan, Europe, and the United States, demonstrating that genetic reassortment can occur in nature between influenza A viruses in pigs, but these resulting reassortants have not yet resulted in an epidemic virus strain in humans (162). While swine influenza viruses have been sporadically transmitted to humans, none of these incidents has resulted in an epidemic disease in humans (35,39,54,55,60,78,81,98,155,193,201,225).…”
Section: History Of Influenza Pandemicsmentioning
confidence: 99%
“…RT-PCR reactions were performed according to previous publications [Wentworth et al, 1994;Daum et al, 2002Daum et al, , 2005Townsend et al, 2006] using a Perkin Elmer 2700 thermocycler (Applied Biosystems, Forest City, CA). The PCR product was purified using QIAquick spin columns using the manufacturer's protocols (Qiagen, Valencia, CA).…”
Section: Genetic and Antigenic Analysismentioning
confidence: 99%
“…Several reports on the transmission of "classical" swine H1N1 viruses, which predominantly circulate in the United States, to humans illustrate the latter possibility. In some cases, human infections with these swine influenza viruses proved to be fatal (Gaydos et al, 1977;Patriarca et al, 1984;Wells et al, 1991;Wentworth et al, 1994). Besides classical swine influenza A viruses, also avian-like swine influenza A (H1N1) viruses, prevalent in Europe since 1979 (Donatelli et al, 1991;Scholtissek et al, 1983;Campitelli et al, 1997) have been shown to be transmitted to humans (De Jong et al, 1986, 1988.…”
Section: Introductionmentioning
confidence: 99%